Effect of intrinsic polymer properties on the photo sensitive organic field-effect transistors (Photo-OFETs) - Kosemen, Zuhal Alpaslan; Kosemen, Arif; Ozturk, Sadullah; Canimkurbey, Betul; San, Sait Eren; Yerli, Yusuf; Tunc, Ali Veysel (ELSEVIER, 2016)
In this work, we have demonstrated how the intrinsic properties of a conjugated polymer can influence the electro-optical characteristics of photo sensitive organic field - effect transistors (Photo-OFETs). Photo-OFETs fabricated with three batches of poly[2-methoxy,5-(3',7'-dimethyl-octyloxy)]-p-phenylene vinylene (MDMO-PPV) were investigated in the scope of our work. Photo-OFETs were fabricated with the polymers, than electrically and electro-optically characterized. It was observed that the channel current and the field-effect mobility increase with increasing polymer molecular weight. Interestingly, the electro-optical characteristics and photo switching properties of the transistors were found to depend on the polydispersity (PDI) of the polymer as well. These results are explained in terms of influences of chain packing, ordering and trap density on the FET switching properties and transistor parameters. (C) 2016 Elsevier B.V. All tights reserved.
Keywords: Photo sensitive organic field-effect transistors (Photo-OFETs); Organic field-effect transistor (OFET); MDMO-PPV; Molecular weight; THIN-FILM TRANSISTORS; MOLECULAR-WEIGHT; PPV-DERIVATIVES; PERFORMANCE; MOBILITY; PHOTOTRANSISTORS; MORPHOLOGY; Engineering; Science & Technology - Other Topics; Optics; Physics